Myelin Oligodendrocyte Glycoprotein-Immunoglobulin G in the CSF: Clinical Implication of Testing and Association With Disability. Issue 1 (28th January 2022) - Kwon, Young Nam; Kim, Boram; Kim, Jun-Soon; Mo, Heejung; Choi, Kyomin; Oh, Seong-il; Kim, Jee-Eun; Nam, Tai-Seung; Sohn, Eun Hee; Heo, Sung Hyuk; Kim, Sang Beom; Park, Key-Chung; et al.
Abstract : Background and Objective: To investigate the clinical relevance of CSF myelin oligodendrocyte glycoprotein-immunoglobulin G (MOG-IgG) testing in a large multicenter cohort. Methods: In this multicenter cohort study, paired serum-CSF samples from 474 patients with suspected inflammatory demyelinating disease (IDD) from 11 referral hospitals were included. After serum screening, patients were grouped into seropositive myelin oligodendrocyte glycoprotein antibody associated disease (MOGAD, 31), aquaporin-4-IgG-positive neuromyelitis optica spectrum disorder (AQP4-IgG + NMOSD, 60), other IDDs (217), multiple sclerosis (MS, 45), and non-IDDs (121). We then screened CSF for MOG-IgG and compared the clinical and serologic characteristics of patients uniquely positive for MOG-IgG in the CSF to seropositive patients with MOGAD. Results: Nineteen patients with seropositive MOGAD (61.3%), 9 with other IDDs (CSF MOG + IDD, 4.1%), 4 with MS (8.9%), but none with AQP4-IgG + NMOSD nor with non-IDDs tested positive in the CSF for MOG-IgG. The clinical, pathologic, and prognostic features of patients uniquely positive for CSF MOG-IgG, with a non-MS phenotype, were comparable with those of seropositive MOGAD. Intrathecal MOG-IgG synthesis, observed from the onset of disease, was shown in 12 patients: 4 of 28 who were seropositive and 8 who were uniquely CSF positive, all of whom had involvement of either brain or spinal cord. Both CSF MOG-IgG titer and corrected CSF/serum MOG-IgG index, but not serum MOG-IgG titer, were associated with disability, CSF pleocytosis, and level of CSF proteins. Discussion: CSF MOG-IgG is found in IDD other than MS and also in MS. In IDD other than MS, the CSF MOG-IgG positivity can support the diagnosis of MOGAD. The synthesis of MOG-IgG in the CNS of patients with MOGAD can be detected from the onset of the disease and is associated with the severity of the disease. Classification of Evidence: This study provides Class II evidence that the presence of CSF MOG-IgG can improve the diagnosis of MOGAD in the absence of an MS phenotype, and intrathecal synthesis of MOG-IgG was associated with increased disability.